The Role of Islamic Religious Education Teachers in Advocating for Muslim Minority Students in Denpasar, Bali - Muthohharoh, Nur Millah; PS, Alaika M. Bagus Kurnia; Putri, Andini Riswanda; Mubaddilah, Ari Fika; Muvid, Muhamad Basyrul (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The role of the teacher as an educator is not only to transfer knowledge to the perpetrators of Islamic education in Denpasar, Bali. They also need to strengthen religion in the aspect of Aqeedah. Because the weakness in practicing and familiarizing with religious practices is considerably less, this study aims to explain how PAI teachers do PAI services in the school setting of Denpasar State Senior High School / Vocational School. This research took four schools as the objects of research. Therefore, this research results from the implication that the teachers are doing service defensively. They give enriching, strengthening, and practicing Aqeedah knowledge to the students (male or female) in Denpasar State High School/Vocational School, Bali. In the presence of strengthening, besides maintaining quantity volume, the quality volume also delivers good impacts when someone has already graduated from an education unit.